2022
DOI: 10.1021/acs.langmuir.2c01947
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent Polymer Nanoparticles Based on Oxazolidine Derivatives for Authentication and Security Marking of Confidential Notes

Abstract: Colloidal materials have widely been used to develop innovative anticounterfeiting nanoinks for information encryption. Latex nanoparticles based on methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (HEMA) bearing hydroxyl functional groups were synthesized via semicontinuous miniemulsion polymerization. The size determination of the nanoparticles and microscopic results showed mostly spherical nanoparticles with a narrow size distribution and a mean size of about 80 nm. Two oxazolidine derivatives wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
(141 reference statements)
0
8
0
Order By: Relevance
“…Polarity of the polymer matrix can significantly affect optical properties of oxazolidine. 2,15,56,69,83,84 This indicates that the polymeric nanoparticles containing oxazolidine molecules are noteworthy candidates of chemosensor applications.…”
Section: Studies On the Optical Properties Of The Polymer Nanoparticl...mentioning
confidence: 99%
“…Polarity of the polymer matrix can significantly affect optical properties of oxazolidine. 2,15,56,69,83,84 This indicates that the polymeric nanoparticles containing oxazolidine molecules are noteworthy candidates of chemosensor applications.…”
Section: Studies On the Optical Properties Of The Polymer Nanoparticl...mentioning
confidence: 99%
“…also prepared photoluminescent polymer particles containing oxazolidine molecules, which were used as anticounterfeiting nanoinks. [ 117 ]…”
Section: Synthesis Of Fluorescent Polymer Particlesmentioning
confidence: 99%
“…Recently, Alidaei-Sharif et al also prepared photoluminescent polymer particles containing oxazolidine molecules, which were used as anticounterfeiting nanoinks. [117] As mentioned above, particles with a range of functional groups on the surface have been synthesized. However, it was found that the increased concentration of amide groups on the particle surface could lead to particle destabilization, which was not conducive to achieving the stability of chromophores with maximum concentration on the particle surface.…”
Section: Post-polymerization Modificationmentioning
confidence: 99%
“…Rhodamine B derivatives, , fluorans, spiropyrans, and crystal violet lactone are some important examples of leuco dye compounds that are generally used in the preparation of thermochromic materials. , Thermochromism is classified into reversible and irreversible categories, where the reversible systems have gained more attention because of their extensive applications based on temperature fluctuations during the day and in different seasons, such as in the military, construction, anticounterfeiting, sensors, etc . For the reversible coloration–decoloration of organic leuco dyes, a three-component system including leuco dye, solvent, and developer is required. , Color developers play the role of chroma, and are often from the category of phenolics (a weak acid such as Bisphenol A), aromatic amines, lauryl gallate, ethyl gallate, carboxylic acids, and Lewis acids that are usually used for the solid state of the thermochromic materials. , Strong proton donors, such as hydrochloric acid, are suitable for both liquid and solid states, and they provide a proton to the color former. A suitable balance is vital between the acidity of the color developer and basicity of the leuco dye .…”
Section: Introductionmentioning
confidence: 99%
“…For the reversible coloration− decoloration of organic leuco dyes, a three-component system including leuco dye, solvent, and developer is required. 22,23 Color developers play the role of chroma, and are often from the category of phenolics (a weak acid such as Bisphenol A), aromatic amines, lauryl gallate, ethyl gallate, carboxylic acids, and Lewis acids that are usually used for the solid state of the thermochromic materials. 14,24−26 Strong proton donors, such as hydrochloric acid, are suitable for both liquid and solid states, and they provide a proton to the color former.…”
Section: Introductionmentioning
confidence: 99%